Medieval music-making and the 'Roman de Fauvel' - Dillon, Emma (Cambridge Cambridge University Press, 2002)
This book explores the role of music in an early fourteenth-century French manuscript (BN, fr. 146). The musical repertories found in this manuscript, particularly those interpolated into the Old French satire, the Roman de Fauvel, are frequently used to illuminate the wider history of French medieval music. This study sets the manuscript against the wider culture of Parisian book-making, showing how in devising new systems of design and folio layout, its creators developed a new kind of materiality in music: it illustrates how music is expressive in ways that are unperformable apart from its visual representation. This study is primarily concerned with the workings of fr. 146; however, it also argues that the new attitudes to (material) music-making embodied in that manuscript serve as a model for exploring other music manuscripts to emerge in late-medieval France.